The First Report of Eustigmaeus johnstoni (Acari: Stigmaeidae) Parasitic Mite of Phlebotominae Sand Flies from Iran. - Mehdi Badakhshan; Javid Sadraei; Vahideh Moin-Vaziri (Tehran University of Medical Sciences, 2013)
Background: Stigmaeids mites have been recorded only on Phlebotominae sand flies up to now. Five species of Eustigmaeus, and three of Stigmaeus were reported on infested sandflies in different country up to the present. Methods: Sand flies collection was done using CDC light trap and sticky paper. The mites were isolated from in- fested specimens, mounted in Puri's medium and identified using reliable keys. Results: A mite infested Phlebotomus papatasi was observed during a study on sandflies of one of the southern provinces of Iran, near to the Persian Gulf. Several scars resulting from mite attachment were found on abdominal tergites of this female sand fly. The mites were identified as Eustigmaeus johnstoni. Conclusion: This parasitic mite is one of the eyeless species, which has a great distribution over the world, reported from Tunisia, Saudi Arabia, Pakistan, Yemen, Cyprus and Palestine. But, this is the first record of this species from Iran.